Videolaryngoscopes differ substantially in illumination of the oral cavity: A manikin study - Barbe MA Pieters; Andre AJ van Zundert (Indian Journal of Anaesthesia, 2016)
Background and Aims: Insufficient illumination of the oral cavity during endotracheal intubation may result in suboptimal conditions. Consequently, suboptimal illumination and laryngoscopy may lead to potential unwanted trauma to soft tissues of the pharyngeal mucosa. We investigated illumination of the oral cavity by different videolaryngoscopes (VLS) in a manikin model. Methods: We measured light intensity from the mouth opening of a Laerdal intubation trainer comparing different direct and indirect VLS at three occasions, resembling optimal to less-than-optimal intubation conditions; at the photographer′s dark room, in an operating theatre and outdoors in bright sunlight. Results: Substantial differences in luminance were detected between VLS. The use of LED light significantly improved light production. All VLS produced substantial higher luminance values in a well-luminated environment compared to the dark photographer′s room. The experiments outside-in bright sunlight-were interfered with by direct sunlight penetration through the synthetic material of the manikin, making correct measurement of luminance in the oropharynx invalid. Conclusion: Illumination of the oral cavity differs widely among direct and indirect VLS. The clinician should be aware of the possibility of suboptimal illumination of the oral cavity and the potential risk this poses for the patient.